Small Group Discussion in Teaching Reading Comprehension at SMA Negeri 2 Toili - Abdul Rabbi Arrasul; Lia Rahmawati; Yusniati N. Sabata; Sitti Hardianti; Armin Haluti (English Education Study Program, 2023)
This research aims to seek whether small group discussion can improve students’ reading comprehension at SMA Negeri 2 Toili or not. The research design of this study was quasi-experimental. The population of this research was eleven grade students of SMA Negeri 2 Toili consisted of 46 students from two classes, XI IPA (experimental) and XI IPS (control). Both classes were taken as the sample. Tests were administered as the research instruments. The results show that experimental class got the highest improvement compared to the control class, from 68,51 became 84,81 in post-test. Therefore, it was obtained the t-counted 7,740 with the significant level 0,05 is 1,680 and the (df) is 44. It means that, t-counted was higher than t-table. In conclusion, Ha was accepted while Ho was rejected. In other words, small group discussion can improve students' reading comprehension achievement at SMA Negeri 2 Toili.